Hydrogen sensors using tapered optical fiber coated with metal oxide nanostructures synthesized via chemical bath deposition technique - Mohd Yahya, Nor Akmar (2018)
In this thesis, novel optical hydrogen (H2) sensors based on manganese dioxide (MnO2), zinc oxide (ZnO) and molybdenum trioxide (MoO3) nanostructures coated on tapered multimode fiber (MMF) via chemical bath deposition (CBD) were developed and investigated. The use of H2 as a clean fuel in various application requires practical and robust sensors as to minimize the risk of explosions associated with its volatile properties. Semiconducting metal oxides (SMO) has been widely used for decades in H2 sensing purpose due to its simplicity in fabrication, low cost and high sensitivity. Nanostructures SMO thin films as sensing layer has been reported to enhance the sensitivity of the sensors due to its high surface area to increase the gas molecules-sensing layer interaction. Typical SMO gas sensors are electrical based in which conductivity changes as it reacts to H2 gas. However, it has certain limitations such as easily affected by electromagnetic interference (EMI) thus compromise the signal response and small sparks could ignite massive explosion if the H2 concentration leaks is more than 4% in the environment. On the other hand, optical sensor which has yet well explored, offers advantages in term of size, light weight, resistant to EMI and resilient in high temperature environment. By integrating the optical transducer with SMO material, it can be employed as a hydrogen gas sensor. There are various methods of producing SMO material such as chemical and physical vapor deposition, RF sputtering, electrochemical deposition and thermal evaporation. These techniques require complicated setup with high operating temperature along with carrier gas during the process and need conductive substrate to perform the procedure. These techniques were also difficult to be implemented on optical fiber. Alternatively, chemical bath deposition method provides simple and easy setup, low operating temperature, low cost and environmental friendly. Therefore the author opted this method to fabricate H2 sensor using tapered optical fiber coated with selected SMO incorporated with palladium (Pd) as a catalyst to enhance the optical responses. In this study, the fabricated sensor is comprised of tapered multimode silica fiber (MMF) as the transducing platform. The tapering process is essential as to enhance the sensitivity to the environment through the interaction of evanescent field on the tapered surface area. The tapered region is then coated with sensing layer which is also important factors that influence the performance of the sensor. For this work, the author focused on a few kinds of SMO material well-known for their electrochromic properties which are manganese dioxide (MnO2), zinc oxide (ZnO) and molybdenum trioxide (MoO3), combined with Pd as the catalytic layer. The SMOs were grown via chemical bath technique and in-situ deposited onto the tapered optical fiber. The morphology of MnO2, ZnO and MoO3 synthesized and deposited on optical fiber were found to be nanograins, nanoflowers and nanogranules which were well distributed over the cylindrical shaped of the tapered optical fiber. The absorbance response of these sensors was characterized in terms of response and recovery times, sensitivity, repeatability and selectivity. It was discovered that the optimum thickness where the sensors of MnO2, ZnO and MoO3 exhibited maximum absorbance response are 300 nm, 280 nm and 250 nm respectively. It was revealed that the annealed sensor demonstrated higher sensitivity compared to as-prepared sensor. It was discovered that annealed Pd/MoO3 coated on tapered optical fiber sensor exhibited highest absorbance increase of 3.80 when exposed to 1% H2 at low operating temperature of 150oC as compared to other metal oxides nanostructures. The response and recovery times recorded were 1.2 min and 3.0 min. The developed MnO2, ZnO and MoO3 nanostructures coated on tapered optical fiber sensor for H2 using CBD technique are the first of its kind according to the author’s knowledge.